2021
DOI: 10.1097/sla.0000000000004998
|View full text |Cite
|
Sign up to set email alerts
|

Pre-transplant T-cell Clonality

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…These infections often manifest as severe mixed infections involving fungi, bacteria, and viruses, which can progress to sepsis. Sepsis represents the most lethal infectious disease and contributes signi cantly to mortality rates in LT patients [7,8]. Kim et al reported that bacteremia developed in 24% of LT recipients [9].…”
mentioning
confidence: 99%
“…These infections often manifest as severe mixed infections involving fungi, bacteria, and viruses, which can progress to sepsis. Sepsis represents the most lethal infectious disease and contributes signi cantly to mortality rates in LT patients [7,8]. Kim et al reported that bacteremia developed in 24% of LT recipients [9].…”
mentioning
confidence: 99%